An Experimental Study on Short Term Durability and Hardened Properties of Baggasse Ash and Fly Ash Based Geo Polymer Concrete - Mohammad Iliyas Mohammad Sayeed; Dr. Vikram A. Patil; Somanagouda R. Takkalaki (International Journal of Engineering and Management Research, 2021)
This project reports the comparison of bagasse ash and fly ash-bagasse ash based on geopolymer concrete. In which cement is fully replaced by pozzolanic material that is rich in silicon and aluminium like fly ash and bagasse ash referred to as “Geopolymer concrete” which is a contemporary material. Geopolymer concrete was actually manufactured by reusing and recycling of industrial solid wastes and by products. Fly Ash, a by-product of coal obtained from the thermal power plant is plenty available worldwide. Fly ash is used as ingredients in concrete which enhance the properties of concrete and utilization of fly ash is helpful for consumption. Bagasse ash is a final waste product of sugar obtained from the sugar mills. The base material, viz. fly ash and Bagasse ash, is activated by alkaline solution that is sodium hydroxide and sodium silicate to produce a binder which is rich in silica and aluminium. Sample 1 is cement. It is replaced by 100% fly ash geopolymer concrete and trial 2 is 10%, 30% & 50% replaced by Bagasse ash in Geopolymer concrete . The project presents the strength and durability of Bagasse ash based Geopolymer concrete and fly ash and Bagasse ash based Geopolymer concrete.